Venous Malformations - Patel, Nihal D.; Chong, Anthony T.; Kolla, Avani M.; Mabud, Tarub S.; Kulkarni, Kopal; Masrouha, Karim; Taslakian, Bedros; Bertino, Frederic J. (Seminars in Interventional Radiology, 2022)
Venous malformations, the most common type of vascular malformation, are slow-flow lesions resulting from disorganized angiogenesis. The International Society for the Study of Vascular Anomalies (ISSVA) classification offers a categorization scheme for venous malformations based on their genetic landscapes and association with congenital overgrowth syndromes. Venous malformations present as congenital lesions and can have broad physiologic and psychosocial sequelae depending on their size, location, growth trajectory, and tissue involvement. Diagnostic evaluation is centered around clinical examination, imaging evaluation with ultrasound and time-resolved magnetic resonance imaging, and genetic testing for more complex malformations. Interventional radiology has emerged as first-line management of venous malformations through endovascular treatment with embolization, while surgery and targeted molecular therapies offer additional therapeutic options. In this review, an updated overview of the genetics and clinical presentation of venous malformations in conjunction with key aspects of diagnostic imaging and treatment are discussed.
Keywords: anomalies; malformations; vascular; venous